2013
DOI: 10.1208/s12249-012-9912-2
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization and Permeability Assessment Based on Caco-2 Monolayers of Self-Microemulsifying Floating Tablets of Tetrahydrocurcumin

Abstract: Abstract. Novel self-microemulsifying floating tablets were developed to enhance the dissolution and oral absorption of the poorly water-soluble tetrahydrocurcumin (THC). Their physicochemical properties and THC permeability across Caco-2 cell monolayers were assessed. The self-microemulsifying liquid containing THC was adsorbed onto colloidal silicon dioxide, mixed with HPMC, gas-generating agents (sodium bicarbonate and tartaric acid), lactose and silicified-microcrystalline cellulose and transformed into ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…This finding confirmed that sponge preparation using lyophilization did not affect the emulsion droplet size, similar to other S-SMEDDS formulations as pellets [11], tablets [12], and other sponges [14]. …”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This finding confirmed that sponge preparation using lyophilization did not affect the emulsion droplet size, similar to other S-SMEDDS formulations as pellets [11], tablets [12], and other sponges [14]. …”
Section: Resultssupporting
confidence: 84%
“…Dynamic light scattering measurements were obtained at a fixed angle of 90° and a temperature of 25 °C [12]. Triplicate samples were each analyzed for 1 min, and for each measurement ran, 12 sub-runs were performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar result was obtained by Sermkaew, et al . (20) who studied floating tablets of tetrahydrocurcumin.…”
Section: Discussionmentioning
confidence: 99%